2013
DOI: 10.1111/iju.12126
|View full text |Cite
|
Sign up to set email alerts
|

Laparoendoscopic single‐site versus conventional transperitoneal laparoscopic pyeloplasty: A prospective randomized study

Abstract: Abbreviations & Acronyms 99mTc-DTPA = technetium99m-diethylene triamine pentaacetic acid BMI = body mass index CTL-P = conventional transperitoneal laparoscopic pyeloplasty LESS = laparoendoscopic single site LESS-P = laparoendoscopic single site pyeloplasty UPJO = ureteropelvic junction obstruction VAS = visual analog scale Objectives: To evaluate the potential benefits of laparoendoscopic single-site pyeloplasty over conventional laparoscopic pyeloplasty. Methods: Between October 2009 and January 2012, 39 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Two of them compared consecutive series (LE]: 3b);[ 13 21 ] one performed a retrospective nonconsecutive study (LE: 4);[ 22 ] one compared a matched cohort (LE: 3a)[ 23 ] one of them was a prospective RCT (LE: 2b). [ 24 ] The methodological quality of the retrospective studies was relatively high, with all the studies reporting at least 7 out of 9 stars, but with a low LE between 3 and 4. Nevertheless, the only RCT study was graded as low quality, reporting 2 out of 5 points [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two of them compared consecutive series (LE]: 3b);[ 13 21 ] one performed a retrospective nonconsecutive study (LE: 4);[ 22 ] one compared a matched cohort (LE: 3a)[ 23 ] one of them was a prospective RCT (LE: 2b). [ 24 ] The methodological quality of the retrospective studies was relatively high, with all the studies reporting at least 7 out of 9 stars, but with a low LE between 3 and 4. Nevertheless, the only RCT study was graded as low quality, reporting 2 out of 5 points [ Table 1 ].…”
Section: Resultsmentioning
confidence: 99%
“…According to this synthesizing evidence, LESS surgery is expected to reduce the morbidity and scarring associated with surgical intervention. Nevertheless, these reports were mostly based on small‐scale studies from selected centers . Therefore, it is difficult to regard LESS surgery as an ideal standard procedure across institutional boundaries.…”
Section: Discussionmentioning
confidence: 99%
“…Several RCTs of urological LESS surgeries compared with conventional laparoscopic procedures were reported. The reported RCTs, including varicocelectomy, 18,19 pyeloplasty, 20 simple nephrectomy 21 and living donor nephrectomy, [22][23][24] although these were relatively small series, suggested that the 18,20,21 and the postoperative pain [18][19][20][21][22][23] were lower, and the time to return to normal activities was shorter [18][19][20][21]24 in the LESS group. Nevertheless, the operative time in the LESS group was longer 18,19,[21][22][23][24] or, at best, equivalent to the conventional group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations